High Density Reflection Spectroscopy – II. The density of the inner black hole accretion disc in AGN. Issue 3 (23rd August 2019) - Jiang, Jiachen; Fabian, Andrew C; Dauser, Thomas; Gallo, Luigi; García, Javier A; Kara, Erin; Parker, Michael L; Tomsick, John A; Walton, Dominic J; Reynolds, Christopher S
ABSTRACT: We present a high density disc reflection spectral analysis of a sample of 17 Seyfert 1 galaxies to study the inner disc densities at different black hole mass scales and accretion rates. All the available XMM–Newton observations in the archive are used. OM observations in the optical/UV band are used to estimate their accretion rates. We find that 65 per cent of sources in our sample show a disc density significantly higher than n e = 10 15 cm −3, which was assumed in previous reflection-based spectral analyses. The best-fitting disc densities show an anticorrelation with black hole mass and mass accretion rate. High density disc reflection model can successfully explain the soft excess emission and significantly reduce inferred iron abundances. We also compare our black hole spin and disc inclination angle measurements with previous analyses.